2014
DOI: 10.1371/journal.pone.0094480
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Wild-Type Saccharomyces cerevisiae Strain TSH1 in Scaling-Up of Solid-State Fermentation of Ethanol from Sweet Sorghum Stalks

Abstract: The rising demand for bioethanol, the most common alternative to petroleum-derived fuel used worldwide, has encouraged a feedstock shift to non-food crops to reduce the competition for resources between food and energy production. Sweet sorghum has become one of the most promising non-food energy crops because of its high output and strong adaptive ability. However, the means by which sweet sorghum stalks can be cost-effectively utilized for ethanol fermentation in large-scale industrial production and commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
(77 reference statements)
0
23
0
Order By: Relevance
“…These results show that it is economically feasible to produce ethanol from sweet sorghum stems by using continuous solid state fermentation and distillation technologies. 1 Using sulfur dioxide for storage [24]. 2 The latter value is the consumption in rectification and dehydration to extract ethanol from 26.3 wt% to 99.5 wt%.…”
Section: Economics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These results show that it is economically feasible to produce ethanol from sweet sorghum stems by using continuous solid state fermentation and distillation technologies. 1 Using sulfur dioxide for storage [24]. 2 The latter value is the consumption in rectification and dehydration to extract ethanol from 26.3 wt% to 99.5 wt%.…”
Section: Economics Analysismentioning
confidence: 99%
“…It also holds considerable versatility, such as absorbing heavy metal from contaminated land or remedying arable land while simultaneously producing cost-effective bioethanol [9][10][11]. However, the spongy and medullary structure causes much higher Saccharomyces cerevisiae TSH-1 frozen with glycerol was used in this study [24]. Yeast cells were pre-cultured in YPD medium (10 g/L yeast extract, 20 g/L glucose, and 20 g/L peptone), incubated at 30 • C with an agitation rate of 200 rpm for 12 h. Then yeast was inoculated into 10 times secondary fermentation medium, incubated at the same temperature with 250 rpm for 6 h. After being washed with sterilized water, the cultivation of yeast was finished when OD 600 = 10 was measured by spectrophotometer.…”
Section: Introductionmentioning
confidence: 99%
“…Saccharomyces cerevisiae yeast has been extensively reported as a responsible organism for the bioconversion of solid wastes (apple pomace, grape pomace, sugar beet pomace, potato peel, sweet sorghum stalks, sugarcane bagasse, food waste, etc.) into bioethanol production under SSF [54,[179][180][181][182][183]. Du et al [181] confirmed the feasibility of scaling up the bioconversion of sweet sorghum stalks by S. cerevisiae from 500 mL to a 127 m 3 rotary drum fermenter and subsequently in a 550 m 3 rotary drum fermenter with 88% of relative theoretical ethanol yield in less than 20 h. Anjani et al [180] presented an interesting integrated bioconversion of potato peel by SSF for the production of bioethanol and manure by employing yeast and fungi (Aspergillus niger, A. variabilis and S. cerevisiae) in an effort to achieve zero waste generation.…”
Section: Bioethanol Productionmentioning
confidence: 99%
“…into bioethanol production under SSF [54,[179][180][181][182][183]. Du et al [181] confirmed the feasibility of scaling up the bioconversion of sweet sorghum stalks by S. cerevisiae from 500 mL to a 127 m 3 rotary drum fermenter and subsequently in a 550 m 3 rotary drum fermenter with 88% of relative theoretical ethanol yield in less than 20 h. Anjani et al [180] presented an interesting integrated bioconversion of potato peel by SSF for the production of bioethanol and manure by employing yeast and fungi (Aspergillus niger, A. variabilis and S. cerevisiae) in an effort to achieve zero waste generation. In Asian regions, palm oil trunk [184], rice straw [185,186], and banana pseudo stem [187] were successfully utilized to produce bioethanol with high yield (84%) by Aspergillus sp.…”
Section: Bioethanol Productionmentioning
confidence: 99%
“…Issatchenkia orientalis [222][223][224] Sweet Sorghum juice Saccharomyces cerevisiae [225] Paddy straw Trichoderma ressei [226] Sugarcane baggase Trichodermaand Penicillium Saccharomyces cerevisiae [227] Ulva fasciata Cladosporium sphaerospermum [228] Food waste Myceliophthora thermophila Saccharomyces cerevisiae [229] Ziziphus jujuba Saccharomyces bayanus [230] to disassociation of each group and make the compound resist for long or sometimes almost as undegradable compound. Though, the application of enzymes to waste treatment was proposed in 1930s [62], was first illustrated in the late 1970s through degradation of parathion using enzyme [63].…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%